Effectiveness of Bontoc Municipal Traffic Enforcers Volunteer Organization in Promoting Road Safety - Ngitew, Marjorie; Guinayen, Jessa; Faba-an, Blaine (International Journal of Criminology & Justice, 2025)
This study evaluates the effectiveness of the Bontoc Municipal Traffic Enforcers Volunteer Organization (BMTEVO) in promoting road safety, while also highlighting the challenges it faces in fulfilling its duties. Using qualitative data, the study collected information from barangay officials, law enforcers, BMTEVO members and community members who have a good understanding of the functions of the BMTEVO members. The findings indicate that while BMTEVO plays an essential role in managing traffic flow and responding to incidents, its overall effectiveness is limited by several issues. Key challenges include a shortage of manpower, equipment shortage and job stability. Additionally, the research offers suggestions for improvement, such as making BMTEVO a permanent organization with ongoing funding, resources and personnel; implementing training programs; and creating clearer policy guidelines; and strengthening collaboration with the local government and volunteer enforcers to improve road safety in Bontoc.